Sex-dependent metabolic and behavioural alterations in a rat model of forced exertion-induced myopathy - Lubbe C; Harvey BH; Viljoen FP; Meyer L; Wolmarans DW (BioMed Central Ltd, 2025)
Background: Mass boma capture (MBC) of ungulates may trigger a metabolic condition known as capture myopathy (CM), resulting in myoglobinuria and hyperthermia (rhabdomyolysis). Its pathobiology is poorly understood, especially the role of contextual reminders; a preclinical model system could thus be useful. Sixty (60) adult Sprague Dawley rats (30 rats per sex), divided into three experimental series (n = 12—24), were exposed to MBC-like exertion, viz., forced treadmill running (FTR) at 75% of VO2MAX (30 m/min) with and without aversive noise (context) until physical exhaustion. Rectal and surface temperatures were measured before and after reaching exhaustion. Urine myoglobin, plasma lactate dehydrogenase (LDH), lactate, and creatine kinase (CK) were measured immediately and 15 days after MBC. Anxiety was assessed in the light-dark and social interaction tests. Results: Male and female MBC rats presented with significant hyperthermia, with females showing significantly increased urine myoglobin immediately after MBC, although this was not sustained until day 15 post MBC. LDH was significantly elevated in female rats at baseline but not day 15 post-MBC. Contextual re-exposure prior to testing on day 15 resulted in significant sex-dependent differences in myoglobin and CK concentrations, with female rats being significantly more affected. Only female rats trended towards increased anxiety-like behaviour immediately post-MBC exposure, which was not sustained until day 15 post MBC. Conclusions: This work builds on previous research using a rodent model of capture myopathy (CM) that confirmed the running protocol to effectively elicite the necessary muscular response. The MBC protocol emphasizes hyperthermia and increased urine myoglobin, sensitivity to contextual reminder (noise), and a trend towards anxiety, particularly in females, highlighting sex-specific physiological responses. By incorporating behavioural and biochemical assessments, acute versus delayed response and environmental triggers, the study enhances model validity and deepens insights into CM-related responses.
Keywords: Contextual reminder; Time-dependence; Capture myopathy; Rhabdomyolysis; Myoglobin; Anxiety